2022
DOI: 10.1371/journal.pone.0255765
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and transcriptomics unravel the mechanism of browning resistance in Agaricus bisporus

Abstract: Agaricus bisporus is widely consumed on the world market. The easy browning of mushroom surface is one of the most intuitive factors affecting consumer purchase. A certain cognition on browning mechanism has been made after years of research. At present, people slow down the browning of mushrooms mainly by improving preservation methods. In addition, breeding is also a reliable way. In the production practice, we have identified some browning-resistant varieties, and we selected a browning-resistant variety to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Meanwhile, a longer fatty-acid length is known to reduce membrane permeability [ 48 ], but this contradicted our transcriptome data in which reducing membrane permeability seemed to induce harder texture than control. Interestingly, in a previous metabolomic analysis, browning-sensitive cultivars of A. bisporus were significantly enriched with unsaturated fatty acids having a chain length of 16 (C16) and 18 (C18) biosynthesis varieties [ 24 ]. In combination, unsaturated forms of long-chain fatty-acids and very-long-chain fatty-acids are expected to accumulate to enhance membrane permeability since our transcriptome gave no sign of desaturase gene expression changes ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a longer fatty-acid length is known to reduce membrane permeability [ 48 ], but this contradicted our transcriptome data in which reducing membrane permeability seemed to induce harder texture than control. Interestingly, in a previous metabolomic analysis, browning-sensitive cultivars of A. bisporus were significantly enriched with unsaturated fatty acids having a chain length of 16 (C16) and 18 (C18) biosynthesis varieties [ 24 ]. In combination, unsaturated forms of long-chain fatty-acids and very-long-chain fatty-acids are expected to accumulate to enhance membrane permeability since our transcriptome gave no sign of desaturase gene expression changes ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic analysis combined with transcriptomic analysis were performed together in easily browning A. bisporus cultivars and hardly browning cultivars. There was no clear correlation between the transcriptome and metabolome, but melanin biosynthesis genes were up-regulated in easily browning cultivars [ 24 ]. To study the effect of a mechanical stimulus on A. bisporus including browning, we used our own material, which also showed a browning phenotype after a mechanical stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional value of Agaricus bisporus changed after UV irradiation, with 47 compounds increasing in concentration and 72 compounds decreasing in concentration [ 131 ]. Looking at the difference between browning tolerant cultivars and common Agaricus bisporus cultivars at the metabolic level, genes such as AbPPo were found to be involved in the regulation of mushroom browning, and higher levels of organic acids, such as butyric acid, were found in brown tolerant Agaricus bisporus cultivars [ 41 ]. In addition, the pH value and alginate content concentration also affected the activity of AbPPo.…”
Section: Application Of Metabolomics In the Field Of Fungal Researchmentioning
confidence: 99%
“…10,11 It has also been found that reactive oxygen species metabolism and phenolic oxidation are the main causes of the tissue browning in Agaricus bisporus, Coprinus comatus, and Flammulina filiformis during the postharvest storage. 2,12 Furthermore, melanin biosynthesis has been proven to contribute to the tissue browning of F. filiformis and A. bisporus. 12 Interestingly, our results indicated that the changes of tissue browning are accompanied by an increasing toughness from the top to the bottom tissues of yellow F. filiformis stipes, indicating that this browning and toughening process is closely related to the differentiation and senescence of stipe cells in these fruiting bodies.…”
Section: Introductionmentioning
confidence: 99%
“…2,12 Furthermore, melanin biosynthesis has been proven to contribute to the tissue browning of F. filiformis and A. bisporus. 12 Interestingly, our results indicated that the changes of tissue browning are accompanied by an increasing toughness from the top to the bottom tissues of yellow F. filiformis stipes, indicating that this browning and toughening process is closely related to the differentiation and senescence of stipe cells in these fruiting bodies. Therefore, even with these findings, it is still not possible to understand how tissue browning and toughness occur during the development of yellow F. filiformis stipes only by investigating the browning of postharvest fruiting bodies under routine short-term storage conditions.…”
Section: Introductionmentioning
confidence: 99%